If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -8m = 4m + -17 Reorder the terms: 7 + -8m = -17 + 4m Solving 7 + -8m = -17 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 7 + -8m + -4m = -17 + 4m + -4m Combine like terms: -8m + -4m = -12m 7 + -12m = -17 + 4m + -4m Combine like terms: 4m + -4m = 0 7 + -12m = -17 + 0 7 + -12m = -17 Add '-7' to each side of the equation. 7 + -7 + -12m = -17 + -7 Combine like terms: 7 + -7 = 0 0 + -12m = -17 + -7 -12m = -17 + -7 Combine like terms: -17 + -7 = -24 -12m = -24 Divide each side by '-12'. m = 2 Simplifying m = 2
| (6x-5)(36x^2-60x+25)=0 | | H-18=17 | | 5(2x-7)=x+5 | | 3x+56=7x+12 | | -14+x=23 | | -3(3s-1)-3=-2(9s+1)-2 | | 9x+4=5x+32 | | x^3+5x^2+5x+25= | | 11x-7=114 | | X-(-45)=16 | | (n-26)2=3n | | -3(5s-6)-18=-3(7s+2)-4 | | 6x^3(x-3)-3x(x-3)= | | -2(5s-5)-10=-3(9s+5)-3 | | X-(-21)=-3 | | X-(-12)=-3 | | X-27=-12 | | 30+90+x=180 | | x^7-3x^6-3x^5= | | 5(t-2)+7t=6(2t+5)-8 | | 54-2x=20x | | 5x+9y=0 | | -2(4s-4)-8=-2(6s+4)-2 | | 5x-29y=23 | | -5+-4k=-21 | | 4x+2=-(x-12) | | (4x+5)-(2x+6)=18 | | 4b-0=0 | | 3x-5=7x+11 | | 7x+4=3x+7 | | .083=4 | | 5x+3y=4 |